2005
DOI: 10.1016/j.femsle.2005.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the endosymbiont ofBlastocrithidia culicisandCrithidia deaneion the glycoconjugate expression and onAedes aegyptiinteraction

Abstract: Blastocrithidia culicis and Crithidia deanei are trypanosomatid protozoa of insects that normally contain intracellular symbiotic bacteria. The protozoa can be rid of their endosymbionts by antibiotics, producing a cured cell line. Here, we analyzed the glycoconjugate profiles of endosymbiont-harboring and cured strains of B. culicis and C. deanei by Western blotting and flow cytometry analyses using lectins that recognize specifically sialic acid and mannose-like residues. The absence of the endosymbiont incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…S. culicis, for example, is able to colonize the insect midgut, to invade the hemocoel and to reach the salivary glands [97], [98]. The presence of the symbiotic bacterium has been shown to influence the interactions between trypanosomatid cells and insect cell lines, explanted guts and host insects [4], [20]. This seems to occur because the endosymbiont influences the glycoprotein and polysaccharide composition of the host, the exposure of carbohydrates on the protozoan plasma membrane, and the surface charge [18], [19], [20], [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. culicis, for example, is able to colonize the insect midgut, to invade the hemocoel and to reach the salivary glands [97], [98]. The presence of the symbiotic bacterium has been shown to influence the interactions between trypanosomatid cells and insect cell lines, explanted guts and host insects [4], [20]. This seems to occur because the endosymbiont influences the glycoprotein and polysaccharide composition of the host, the exposure of carbohydrates on the protozoan plasma membrane, and the surface charge [18], [19], [20], [21].…”
Section: Resultsmentioning
confidence: 99%
“…The endosymbiont-harboring strains exhibit a differential surface charge and carbohydrate composition than the aposymbiotic cells obtained after antibiotic treatment [18], [19]. Furthermore, the presence of the symbiotic bacterium influences the protozoan interaction with the insect host, which seems to be mediated by gp63 proteases, sialomolecules, and mannose-rich glycoconjugates [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of equal expression may be correlated to the parasites growth and/or cell cycle phases, since flagellate cultures were not synchronized. Furthermore, the occurrence of distinct subpopulations could alternatively denote a different expression of surface gp63-like molecules in the different developmental stages or even a diminished accessibility to external ligands in cell subsets, as previously reported for other trypanosomatid cell surface molecules [12,27]. Conversely, the extracellular isoform can be released from parasite cells by two mechanisms that follow the classic secretory pathway with routing of gp63 from the endoplasmic reticulum to the Golgi network and then into the flagellar pocket.…”
Section: Metallopeptidases: Gp63-likementioning
confidence: 77%
“…It is well known that the symbiont interferes with several aspects of the host trypanosomatid physiology [233], including the production of proteolytic enzymes [10,23,26]. In this sense, previous studies showed that endosymbiont-bearing strains are more efficient in binding to insect cell lines and midguts, as compared to symbiotic free strains, which is probably related to differential expression of surface molecules [27,234]. For example, the endosymbiont of C. deanei influences the expression of surface gp63 molecules.…”
Section: Metallopeptidases: Gp63-likementioning
confidence: 99%
“…At least 50 000 cells were analyzed per sample with four repeats per experiment. Control cells were first analyzed to determine their auto fluorescence (Santos et al , 2002a, b; d'Avila‐Levy et al , 2005). Windows Multiple Document Interface Flow Cytometry Application ( winmdi ) was used to generate the histogram.…”
Section: Methodsmentioning
confidence: 99%